The corrosion resistance and microstructure of ubm system-deposited nbxsiynz thin films (2012)
NbxSiyNz thin film nanostructure was grown using the unbalanced magnetron sputtering (UBM) technique with varying Si content. Corrosion resistance was evaluated by potentiodynamic polarisation technique in a 3% NaCl solution. Microstructure was analysed by X-ray diffraction (XRD), scanning electron microscopy (SEM) and laser scanning microscopy. Chemical composition was ascertained by X-ray fluorescence (XRF) technique. The results showed that deposition rates increased with higher Si content. A microstructural change was observed for greater than 5% Si content through the transition from a crystalline to an amorphous structure in the thin films. Corrosion test results demonstrated that the thin films having the highest silicon content had better corrosion resistance.